Delirium as a complication of the surgical intensive care - Horacek R; Krnacova B; Prasko J; Latalova K (Neuropsychiatric Disease and Treatment)
Rostislav Horacek,1 Barbora Krnacova,2 Jan Prasko,2 Klara Latalova2 1Department of Central Intensive Care Unit for Surgery, 2Department of Psychiatry, Faculty of Medicine and Dentistry, University Hospital Olomouc, Palacky University Olomouc, Czech Republic Background: The aim of this study was to examine the impact of somatic illnesses, electrolyte imbalance, red blood cell count, hypotension, and antipsychotic and opioid treatment on the duration of delirium in Central Intensive Care Unit for Surgery.Patients and methods: Patients who were admitted to the Department of Central Intensive Care Unit for Surgery in the University Hospital Olomouc from February 2004 to November 2008 were evaluated using Riker sedation–agitation scale. Their blood pressure, heart rate, respiratory rate, and peripheral blood oxygen saturation were measured continually, and body temperature was monitored once in an hour. The laboratory blood tests including sodium, potassium, chlorides, phosphorus, urea and creatinine, hemoglobin, hematocrit, red and white blood cell count, and C-reactive protein, albumin levels and laboratory markers of renal and liver dysfunction were done every day. All measurements were made at least for ten consecutive days or longer until the delirium resolved.Results: The sample consisted of 140 consecutive delirious patients with a mean age of 68.21±12.07 years. Delirium was diagnosed in 140 of 5,642 patients (2.48%) admitted in CICUS in the last 5 years. The median duration of delirium was 48 hours with a range of 12–240 hours. Statistical analysis showed that hyperactive subtype of delirium and treatment with antipsychotics were associated with prolonged delirium duration (hyperactive 76.15±40.53 hours, hypoactive 54.46±28.44 hours, mixed 61.22±37.86 hours; Kruskal–Wallis test: 8.022; P<0.05). The duration of delirium was significantly correlated also with blood potassium levels (Pearson’s r=0.2189, P<0.05), hypotension (hypotension 40.41±30.23 hours versus normotension 70.47±54.98 hours; Mann–Whitney U=1,512; P<0.05), administration of antipsychotics compared to other drugs (antipsychotics 72.83±40.6, benzodiazepines 42.00±20.78, others drugs, mostly piracetam 46.96±18.42 hours; Kruskal–Wallis test: 17.39, P<0.0005), and history of alcohol abuse (with a history of abuse 73.63±45.20 hours, without a history of abuse 59.54±30.61 hours; Mann–Whitney U=1,840; P<0.05). One patient had suffered from complicated postoperative hypostatic pneumonia and died due to respiratory failure (patient with hypoactive subtype). According to the backward stepwise multiple regression, the best significant predictors of duration of the delirium were the hypotension, type of psychopharmacs, type of delirium, the daily dose of opioids, a combination of psychopharmacs, history of alcohol abuse, plasma level of potassium, anemia, hyperpyrexia, and plasma level of albumin, reaching statistical significance (analysis of variance: F=5.205; df=24; P<0.005; adjusted r2=0.637).Conclusion: The hyperactive type of delirium, hypotension, usage of antipsychotics, the higher daily dose of opioids, a combination of psychopharmacs, history of alcohol abuse, low blood levels of potassium, anemia, hyperpyrexia, and hypoalbuminemia in the CICUS were associated with longer duration of delirium.Keywords: delirium, care duration, intensive care, risk factors, treatment, antipsychotics